2012
DOI: 10.1136/jclinpath-2012-200695
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma and salivary cortisol levels in patients with oral cancer and their association with clinical stage

Abstract: These results indicate a dysregulation of cortisol secretion in patients with oral cancer and suggest that this hormone can be a biomarker associated with the disease's clinical status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…In SCC group stress and depression level was higher than normal when assessed by DAS Scale, which correlated with Hann D et al 29 in (2002) who observed higher depression score in cancer patients of older age group compared to females and younger age patients. Also the salivary cortisol level was higher than normal range which was consistant with Bernabe DG et al 30 who observed higher plasma and salivary cortisol level in oral squamous cell carcinoma patients compared to oropharyngeal carcinoma, leukoplakia, smokers and healthy patients.…”
Section: Discussion:-supporting
confidence: 73%
“…In SCC group stress and depression level was higher than normal when assessed by DAS Scale, which correlated with Hann D et al 29 in (2002) who observed higher depression score in cancer patients of older age group compared to females and younger age patients. Also the salivary cortisol level was higher than normal range which was consistant with Bernabe DG et al 30 who observed higher plasma and salivary cortisol level in oral squamous cell carcinoma patients compared to oropharyngeal carcinoma, leukoplakia, smokers and healthy patients.…”
Section: Discussion:-supporting
confidence: 73%
“…Cortisol, a steroid hormone secreted by the adrenal cortex, is used to assess hypothalamic-pituitary-adrenal axis function and is a reliable measure of physiological stress. [18] Cortisol affects multiple physiological processes, including metabolic and immune responses (e.g., suppressing T lymphocyte functions and natural killer cell cytotoxicity). Women living with breast cancer have higher cortisol levels as compared to healthy women, and higher cortisol levels are associated with greater disease severity in women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other systemic effects of tumor-associated inflammation have been noted, especially alteration of the hypothalamic-pituitary-adrenal (HPA) axis. Altered cortisol patterns have been identified in ovarian cancer patients (Weinrib et al, 2010), endometrial cancer patients (Sannes et al, 2013), and oral cancer patients (Bernabé et al, 2012) prior to treatment. In ovarian cancer patients, these patterns are significantly associated with IL-6 concentrations in the ascites fluid (Schrepf et al, 2015) and in plasma (Lutgendorf et al, 2008).…”
Section: Cancer Patients Prior To Treatmentmentioning
confidence: 99%